EVALUATION OF THE IMPLEMENTATION OF THE SUPPLEMENTARY FOOD PROGRAM AS AN EFFORT TO IMPROVE THE NUTRITION OF STUNTING TODDLERS IN THE WORK AREA OF THE PUSKESMAS KARANGDORO - 'Ulya, Niswah Attazkiatul; Maharani, Chatila (MEDIKORA, 2024)
The Indonesian Nutrition Status Survey (SSGI) in 2021 the prevalence of stunting was 24.4% and in 2022 the prevalence decreased by 2.8% to 21.6%. The prevalence of stunting in Central Java has decreased from 20.9% in 2021 to 20.8% in 2022. Karangdoro Health Center in 2023 has a prevalence of stunting with a total of 614 toddlers. One of the efforts in handling stunting cases is through a supplementary feeding program to achieve optimal nutritional status and prevent stunting. This study aims to determine the inputs, processes, outputs, and outcomes in the implementation of the supplementary feeding program for stunting toddlers in the Karangdoro Puskesmas working area, East Semarang District in 2024. Using a qualitative approach with a case study design, 17 informants were selected by purposive sampling. Data collection using in-depth interviews, observation, and documentation was conducted in September 2024. The results of the input, process, output, and outcome research show that the implementation of the PMT program is good, but there are several things that have not run optimally such as the lack of educational media facilities and infrastructure, refusal to provide additional food from families of toddlers, lack of supervision and monitoring from nutrition implementers, as well as program achievements that have not been maximized and the decline in stunting rates that are still fluctuating. The supplementary feeding program in the Karangdoro Puskesmas working area requires improvement and monitoring or supervision from the puskesmas.